The relationship between training and development with organizational performance among non- executive employees at Ministry of Tourism Sarawak / Hamizah Abdul Rahman - Abdul Rahman, Hamizah (2016)
This research is being conducted with the purpose to measure the relationship of Training and Development towards Organizational Performance at Ministry of Tourism Sarawak. There are two objectives in this study, which were to identify the level of agreeableness on the factors of Training and Development towards Organizational Performance and to study the relationship between Training and Development with Organizational Performance. Questionnaire was used as research instrument. Meanwhile, the sample size will be 70 non-executive employees. Based on this finding, the results obtained indicate that Training and Development has a positive relationship on Organizational Performance. Recommendation and conclusion form the last part of this paper.